Electrostatic carrier doping of charge-ordered YbFe2O4 thin films using ionic liquids. (15th July 2021) - Fujiwara, Kohei; Hori, Tatsuya; Tanaka, Hidekazu
Abstract: We report the modulation of electrical properties of charge-ordered YbFe2 O4 films using electrostatic carrier doping. By utilizing the current switching effect under a high DC electric field as a probe, we detected the charge-ordered phase in the c -axis-oriented YbFe2 O4 films grown by pulsed-laser deposition. A three-terminal electric double-layer device with a thin channel of YbFe2 O4 and an ionic liquid (IL) gate dielectric showed reversible modulation of channel conductance under a positive gate voltage. Furthermore, we demonstrated that conductance modulation could be enhanced by customizing the molecular structure of the IL.